Gravidade f(R) e a energia escura de Tsallis - Ens, Peter Silva (2021)
This dissertation obtains results, which describe the evolution of the universe, by combining a modified theory of gravitation with an alternative form for the holographic density of dark energy. Starting with a review of how Einstein’s equations can be obtained from a variational principle. After that, it presents one of the most common ways of modifying general relativity (f(R)) and its equations of motion. Then Tsallis’ proposal for a new form of dark energy is presented. Finally, these areas are joined in a numerical calculation in order to obtain solutions, for the scale factor and the state parameter, for multiple cases and to analyze such results.